The study on hemodynamic effect of series type LVAD on aortic blood flow pattern: a primary numerical study. Issue 2 (December 2016) - Zhang, Qi; Gao, Bin; Chang, Yu
Abstract Background Left ventricular assist device (LVAD) has become an alternative treatment for end-stage heart failure patients. Series type of LVAD, as a novel LVAD, has attracted more and more attention. The hemodynamic effects of series type LVAD on aortic blood pattern are considered as its important characteristics; however, the precise mechanism of it is still unclear. Methods To clarify the hemodynamic effects of series type LVAD on aortic blood flow pattern, a comparative study on the aortic blood flow pattern and hemodynamic states were carried out numerically for two cases, including series type LVAD support and normal condition. The steady-state computational fluid dynamic (CFD) approach was employed. The blood flow streamline, blood velocity vector and distribution of wall shear stress (WSS) were calculated to evaluate the differences of hemodynamic effects between both conditions. Results The results demonstrated that the aortic flow pattern under series type LVAD showed significant different from that of normal condition. The strength of aortic swirling flow was significantly enhanced by the series type LVAD support. Meanwhile, the rotating direction of swirling flow under LVAD support was also dominated by the rotating direction of series type LVAD. Moreover, the blood velocity and WSS under LVAD support were also significantly enhanced, compared with that under normal condition. Conclusion The hemodynamic states, including the aortic swirling flow characteristic, was significantly dominated by LVAD support. Present investigation could provide not only a useful information on the vascular complications caused by LVAD support, but also provide a useful guide for optimal the structure of the series type LVAD.